PHARMACOLOGICAL AND CLINICAL PROFILE OF ACAMPROSATE-A DRUG USED FOR ALCOHOL ABUSE: A REVIEW - SATYANAND TYAGI; SACHIN KUMAR; AMIT KUMAR; MOHIT SINGLA (International Journal of Pharma and Bio Sciences, 2010)
Alcoholism, also known as alcohol dependence is a disabling addictive disorder. It is characterized by compulsive and uncontrolled consumption of alcohol despite its negative effects on the drinker's health and social standing. Similar to other drug addictions, alcoholism is medically defined as a treatable disease. The term 'alcoholism' is a widely used term, first coined in 1849 by Magnus Huss, but in medicine was replaced in by 'alcohol abuse' and 'alcohol dependence' in the 1980s DSM (Diagnostic and Statistical Manual of Mental Disorders) Similarly in 1979 an expert World Health Organization committee disfavored the use of 'alcoholism' as a diagnostic entity, preferring the category of "alcohol dependence syndrome". FDA approved drug Acamprosate is used for treating alcohol dependent individuals seeking to continue to remain alcohol-free after they have stopped drinking. Acamprosate may not be effective in patients who are actively drinking at the start of treatment, or in patients who abuse other substance in addition of alcohol. In the present article, we have focused on pharmacological profile of drug Acamprosate along with its clinical utility in the treatment of alcohol abuse.